The application of mixed methods research in public administration : opportunity missed or taken? - Hlongwane, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
The aim of this paper is to analyse the extent to which public administration scholars make use of mixed methodology in conducting their research. Essentially, mixed methodology entails combining qualitative and quantitative research methods in order to attain research objectives. For the purpose of this paper, an unobtrusive research was undertaken. In other words, no human participants were involved. To be precise, a secondary data analysis was conducted in order to determine the extent to which public administration scholars use mixed methodology in public administration research. In order to attain the objective of this research paper, 239 scholarly peer reviewed journal articles were reviewed in order to establish the methodology applied. This involved an analysis of articles published in 2018 and 2019 volumes of the four academic journals in the field of public administration, namely: Journal of Public Administration and Development Alternatives, Administration Publica, Journal of Public Administration, and the International Review of Public Administration. The findings indicate that out of 239 articles published in the aforementioned journals, only 20 articles applied mixed methodology in gathering empirical data. The other issue is that in some instances where researchers used mixed methodology in their articles, they did not state any specific variant of mixed methods adopted. Such explanations would assist readers in appreciating the research results and findings. Based on available evidence, this paper concludes that public administration scholars have indeed missed an opportunity to make use of and benefit from using mixed methodology. Therefore, it is important for public administration scholars to consider rigorous application of mixed methodology research in order to obtain in-depth information regarding any subject of investigation
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Mixed method research; Public Administration; qualitative; quantitative; Public administration; Qualitative